Vpliv dveh ur atletike na gibalno/športno aktivnost otrok - Volmut, Tadeja; Šimunič, Boštjan (Revija za elementarno izobraževanje, 2016)
The impact of two hours of athletics weekly on the physical / sporting activity for children. The purpose of our study was to investigate if organised physical activity of athletics increase the overal amount and intensity of physical activity during and after an athletics session. Using an accelereometer we measured weekly physical activity in 22 children (11 boys, aged 6.6 ± 1.2 years), including two hours of organised athletics. During athletics physical activity reached 1787 ± 620 (without athletics 615,5 ± 116,6) counts/minute, with most prevalent physical inactivity (29 ± 11,7 minutes) and moderate to vigorous physical activity (19,0 ± 8,9 minutes). Two weekly hours of athletics increased average daily time of moderate to vigorous physical activity (16 %; P < 0,001) and decreased the time of physical inactivity (–10 %; P < 0,001). Athletics contrbutes to achieving physical activity norms; however, more focus should be placed on increasing the intensity of physical activity during organised hours of athletics.
Keywords: accelerometer; organised class; children; athletics